Milan and the military anarchy (Studi di storia medioevale e di diplomatica - Nuova Serie, 2021)
According to the common opinion, the status of base of operations accorded to Milan at the time of Gallienus prefigures the pre‐eminent role of the city that will emerge during the Tetrarchic age; notwithstanding, this historical period has been little investigated so far due to the scarcity of available documentation. Therefore, this paper aims to study the history of Milan and, more generally, of the Cisalpina between the invasion of the Alamanni in 259‐260 and the age of Diocletian. During these years, northern Italy seems to act as a driving force of macro‐regional events which concern the internal struggles to achieve the imperial power and the conflicts with those barbarians who were militarily active along the borders. Particular attention will be paid to Aureolus: his military ducatus, which was extended at least to the Raetia, prefigures the connection be‐ tween the Raetia and Italy that will be institutionalised in late antiquity.
Keywords: Mediolanum; Aureolus; Gallienus; Raetia; Alamanni